MIKROMORFOLOŠKE KARAKTERISTIKE MASTOCITA U TIGEMINALNIM I HUMANIM SIMPATIČKIM GORNJIM VRATNIM GANGLIONIMA - Ćetković, Mila; Milosavljević, Aleksandra; Boljanović, Jelena; Laketić, Darko; Simić, Marko; Bogosavljević, Nikola; Mirčić, Aleksandar; Milisavljević, MILAN (Medical Research, 2025)
Introduction: Mastocytes (Ms) are usually localized close to microvessels and terminals of the nerves innervating meninges and visceral organs. The granules of Ms contain numerous mediators that affect nerve cells and modify their reactions. Aim: Our study was conducted with the aim to analyze the presence and localization of Ms, and mastocytes density (MsD) in three segments of the human trigeminal ganglions (TGs): ophthalmic, maxillary and mandibular, as well as in two parts: upper and lower, of the sympathetic superior cervical ganglions (SSCGs), and to establish the correlation between the studied parameters.Material and Methods: Five TGs and five SSCGs of adult individuals were processed for this histochemical and immunohistochemical analysis. The sections are serially sliced and stained with hematoxylin and eosin and the trichrome method of Masson, as well as for the mastocyte tryptase immunostaining.Results: The average number of tryptase-positive (Tryp+) Ms in the marked fields on the microscope, the MsD, was 1.4 in the ophthalmic parts, 1.3 in the maxillary parts, and 1.5 in the mandibular parts of TGs. The average number of Tryp+ Ms in fields on the microscope, the MsD, was 4.35 in the upper segments, and 4.45 in the lower segments of SSCGs. The distributions of Ms in three parts of the human TGs and two segments of the SSCGs were evenly distributed with no special morphological peculiarities. This is the first micromorphological analysis of the Tryp+ Ms and MsD in human TGs and SSCGs.Conclusion: We found statistically significant differences in MsD of Tryp+ Ms between TG and SSCG (p = 0.000). MsD in two parts of the SSCG was significantly higher than MsD in three parts of TG.
Keywords: micromorphological analysis, mastocytes, mastocytes density, sympathetic superior cervical ganglion, trigeminal ganglion